2018
DOI: 10.1021/acs.jmedchem.8b00161
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Based Optimization of Metabotropic Glutamate Receptor 2 (mGluR2) Positive Allosteric Modulators in the Absence of Structural Information

Abstract: Metabotropic glutamate receptor 2 (mGluR2) positive allosteric modulators (PAMs) have been implicated as potential pharmacotherapy for psychiatric conditions. Screening our corporate compound deck, we identified a benzotriazole fragment (4) that was rapidly optimized to a potent and metabolically stable early lead (16). The highly lipophilic character of 16, together with its limited solubility, permeability, and high protein binding, however, did not allow reaching of the proof of concept in vivo. Since furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Alignment of the available pharmacophores revealed that the N-acceptor feature of the benzimidazole ring was replaced by carbonyl oxygen in the dihydropyrazino-benzimidazolone system (Figure A). Pharmacophore alignment of benzotriazole chemotypes including an optimized Merck compound ( 15 ), our advanced lead ( 13 ), and the optimized fragment ( 14 ) suggested that in addition to the N-acceptor feature, a partial negative charge is preferred (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alignment of the available pharmacophores revealed that the N-acceptor feature of the benzimidazole ring was replaced by carbonyl oxygen in the dihydropyrazino-benzimidazolone system (Figure A). Pharmacophore alignment of benzotriazole chemotypes including an optimized Merck compound ( 15 ), our advanced lead ( 13 ), and the optimized fragment ( 14 ) suggested that in addition to the N-acceptor feature, a partial negative charge is preferred (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…In order to develop powerful tools for translational mGluR2 research, we followed a fragment-based optimization strategy. In our previous work, we demonstrated that the optimization of a fragment size hit to a large lead ( 13 ) was less fruitful than a fragment optimization strategy which yielded 14 , a potent mGluR2 PAM fragment reported for the first time (Figure ). Results achieved in the absence of structural information prompted us to extend this approach for the dihydropyrazino-benzimidazolone core.…”
Section: Introductionmentioning
confidence: 99%
“…SIB1893 [117] appeared to be an mGlu 5 NAM; however, TCN238 [118] turned to be an mGlu 4 PAM. In addition, VU0418506 [119] and its close analogue 1‐benzyl‐1 H ‐1,2,3‐benzotriazole ( 57 ) [120] were reported as optimized mGlu 4 selective PAM and as a HTS hit for mGlu 2 , respectively. Pittolo and co‐workers described a potent mGlu 5 NAM ( 58 ) [121] during the development of photoisomerizable ligands from an mGlu 4 PAM VU0415374 [122] .…”
Section: Ligand Modifications Resulting In Subtype Switchingmentioning
confidence: 99%
“…A recent example of fragment optimization using only chemical optimization in the absence of a crystal structure was reported by Szabó et al (2018). The researchers identified a fragment-like hit in a functional assay looking for positive allosteric modulators of metabotropic glutamate receptor 2.…”
Section: Chemical Approachesmentioning
confidence: 99%